De l'éducation permanente à la certification permanente - Frédéric Neyrat (Les éditions de la Maison des sciences de l'Homme, 2003)
Since the promulgation of the « loi de modernisation sociale » in January 2002, the French education system is now able to take into account personnal and professionnal skills acquired through experience. Whole degrees can now be validated without the agency of the teaching system. In France, these new measures organizing the validation of acquired experience (VAE) are rationalized in the name of the battle against exclusion (experience being the second chance for obtaining certification) but are, in reality, part and parcel of a policy for lifelong education and training codefined by the Europan Commission and the OECD. This article shows that this injunction for the formal system to recognize other modes of non formal or informal education, via the VAE also vehicles a discours on the necessity to seek other means of financing the formal system, other than through state funds, and more especially higher education. It has now become obvious that this is the real motivation for change.